Relationship between Nutritional Status and Living Conditions with the Risk of Tuberculosis in Children (KEMAS: Jurnal Kesehatan Masyarakat, 2023)
Children are very susceptible to TB infection. One of the causes of TB in children is nutritional status. Poor one causes a weak immune system, making contracting tuberculosis easier. In addition, living conditions can spread to children due to contact with active pulmonary TB in one household. This study aims to determine the relationship between nutritional status and living conditions with TB incidence in children. This case-control study involved 76 samples consisting of 38 cases and 38 controls. Research subjects were taken using the purposive sampling method. The subjects were children aged 0-18 years diagnosed with TB based on anamnesis, physical examination, tuberculin skin test, and chest X-ray. This study was conducted at Bhakti Medicare Sukabumi Hospital from July to December 2019. The results of the Chi-square test found that there was a relationship between nutritional status (p=0.023), ventilation area (p=0.043), and humidity (p=0.001). There is no relationship between age (p=0.639), gender (0.490), parental education (p=0.803), lighting (p=0.200), temperature (0.260), density (p=1.000), and type of floor (p=0.240).